Pengaruh Online Consumer Reviews dan Influencer terhadap Keputusan Pembelian Melalui Aplikasi Tiktok pada Mahasiswa Universitas Pendidikan Ganesha - Br Sembiring, Ika Tindria; Suwendra, I Wayan (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2024)
This research aims to determine the influence of (1) online consumer reviews on purchasing decisions via the TikTok application; (2) Influencers on purchasing decisions through the TikTok application; and (3) Online consumer reviews and influencers on purchasing decisions through the TikTok application. This research uses a causal quantitative research design. The population in this study was 2425 students from the class of 2019 at Ganesha Education University. The technique used in sampling is purposive sampling. The sample in this study amounted to 100 people. The data collection method was carried out through distributing questionnaires. Data were analyzed using multiple linear regression analysis. The results of this research show that (1) Online Consumer Reviews have a significant influence on purchasing decisions via the TikTok application; (2) Influencers have a significant influence on purchasing decisions through the TikTok application; and (3) Online Consumer Reviews and Influencers have a significant influence on purchasing decisions via the TikTok application